How to evaluate the medical certification of death in a hospital: an analysis of 53 death certificates at AIIMS, Bhopal, India - Patel, Narendra; Patel, Sweta; Vidua, Raghvendra Kumar; Arora, Arneet; Tamaria, K. C. (International Journal Of Community Medicine And Public Health, 2017)
Background: The AIIMS Bhopal has been established under PMSSY to provide the quality health care services. However, since the inception of hospital services from November 2014 till the month of October 2016 a total of 53 patients died due to various causes. The objective was to find out the different causes of death and its documentation at a tertiary care hospital in order to establish common causes of mortality and reporting errors in standard documentation of the death and feedback in this regard. Methods: This is a retrospective study with evaluation of death certificates in 53 deaths. The errors were analyzed as per the Haque’s scale and the scale devised by the authors. Results: The major cause of death reported was multiorgan failure where more than one system was affected As per the Haque’s scale the errors reported were for Grade 0 in 0%, Grade 1A in 31.03%,Grade 1B in 100%,Grade II in 79.31%,Grade III in 68.97%,Grade IV in 79.31% and Grade V in 62.07% of total death certificates. Conclusions: The certifying doctors must be adequately trained and/or fill the death certificate under the supervision of experts to ensure proper entries to avoid any kind of contraventions, confusion and conflicts.